1982
DOI: 10.1016/0160-4120(82)90030-7
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant emission rates from indoor combustion appliances and sidestream cigarette smoke

Abstract: Particulate and gaseous emissions from indoor combustion appliances and smoking can elevate the indoor concentrations of various pollutants.Indoor pollutant concentrations resulting from operating one of several combustion appliances, or from sidestream tobacco smoke, were measured in a 27-m 3 environmental chamber under varying ventilation rates. 7he combustion appliances investigated were gas-fired cooking stoves, unvented kerosene-fired space heaters, and unvented natural gas-fired space heaters. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 2 publications
2
32
0
1
Order By: Relevance
“…14 In work performed at LBL tests on a gas-fired space heater showed emissions of CO to be 655 /ig/Kcal. 27 In this same work, the LBL workers showed that sidestream cigarette smoke .produced 130 jug CO/mg of tobacco burned. This value is about half that reported in the NAS report.…”
Section: Carbon Monoxidementioning
confidence: 93%
“…14 In work performed at LBL tests on a gas-fired space heater showed emissions of CO to be 655 /ig/Kcal. 27 In this same work, the LBL workers showed that sidestream cigarette smoke .produced 130 jug CO/mg of tobacco burned. This value is about half that reported in the NAS report.…”
Section: Carbon Monoxidementioning
confidence: 93%
“…2 /1000 Btu/h heater capacity, a recommendation of some manufacturers, should be provided to minimize the accumulation of contaminants. Purchasing an oversized heater or operating a heater in a smaller room than that for which it was intended will result in high, and possibly unsafe concentrations of air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…First, residential combustion sources have been shown to be relatively weak sources of formaldehyde in emissions tests, 33 and no significant contribution of these sources to indoor formaldehyde levels has been ascertained in several large field studies. (Table III) showed no correlation (R = -0.01) with weekly averages of simultaneous measurements of indoor NO2.…”
Section: Influence Of House and Household Factorsmentioning
confidence: 99%